2016
DOI: 10.1080/14763141.2015.1123766
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Microsoft Kinect® camera system for measurement of lower extremity jump landing and squatting kinematics

Abstract: Cost effective, quantifiable assessment of lower extremity movement represents potential improvement over standard tools for evaluation of injury risk. Ten healthy participants completed three trials of a drop jump, overhead squat, and single leg squat task. Peak hip and knee kinematics were assessed using an 8 camera BTS Smart 7000DX motion analysis system and the Microsoft Kinect® camera system. The agreement and consistency between both uncorrected and correct Kinect kinematic variables and the BTS camera s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
2
16
0
Order By: Relevance
“…However, these studies assess movement patterns rather than specific joint angles, and use visual observation as reference standard rather than conventional 3D motion analysis [ 47 , 48 ]. Similar to this study, other markerless 3D MoCap tools such as the Kinect V2, have demonstrated stronger validity for sagittal plane kinematics than for the frontal plane during the single leg squat [ 45 , 49 ]. The difference in accuracy of sagittal plane versus frontal and transverse plane measurements can be explained from a biomechanical point of view.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, these studies assess movement patterns rather than specific joint angles, and use visual observation as reference standard rather than conventional 3D motion analysis [ 47 , 48 ]. Similar to this study, other markerless 3D MoCap tools such as the Kinect V2, have demonstrated stronger validity for sagittal plane kinematics than for the frontal plane during the single leg squat [ 45 , 49 ]. The difference in accuracy of sagittal plane versus frontal and transverse plane measurements can be explained from a biomechanical point of view.…”
Section: Discussionsupporting
confidence: 68%
“…This study shows that easily accessible technology is likely to enter the market for a broad audience of professionals from different fields. The recent research interest from orthopedic and neurologic rehabilitation specialists in this type of technology shows that there is a loud call for quantification of many parameters in their specific patient populations [ 2 , 4 , 9 , 17 , 19 , 20 , 21 , 31 , 34 , 45 ]. Every movement related health problem would thus likely have its own clinical relevant movement parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, depth cameras have been integrated into rehabilitation protocols in patients with different diseases, such as stroke survivors [13,21,22,23], Parkinson’s disease [24], and cerebral palsy [25], and in different movements such as jumping [26], walking [21,27,28], running [27] or even for transferring a person to a wheelchair [29]. Among the most similar works to our proposal, the paper series from Clark et al [30,31] also presents the Kinect camera as a potential instrument for the assessment of standing balance and postural control.…”
Section: Introductionmentioning
confidence: 99%
“…Both the Xbox 360 and Xbox One Kinect provide a software development kit (SDK) for automated 3D human-pose estimation [4]. Automatic human-pose estimation using Microsoft's SDK has been assessed in many sport and health applications, including functional movement assessment [5] and gait analysis [6]. Whilst automatic human-pose estimation is an extremely useful tool for movement-based analyses, measurement agreement has limited its use as a surrogate motion capture system [5].…”
Section: Introductionmentioning
confidence: 99%
“…Automatic human-pose estimation using Microsoft's SDK has been assessed in many sport and health applications, including functional movement assessment [5] and gait analysis [6]. Whilst automatic human-pose estimation is an extremely useful tool for movement-based analyses, measurement agreement has limited its use as a surrogate motion capture system [5]. Moreover, whilst joint position estimates contain error [4], the model-based nature of estimation can exacerbate errors for persons deviating from this model (i.e., stature, shape, etc.).…”
Section: Introductionmentioning
confidence: 99%